All-Optical Electrophysiology in hiPSC-Derived Neurons With Synthetic Voltage Sensors - Puppo, Francesca; Sadegh, Sanaz; Trujillo, Cleber A.; Thunemann, Martin; Campbell, Evan P.; Vandenberghe, Matthieu; Shan, Xiwei; Akkouh, Ibrahim A.; Miller, Evan W.; Bloodgood, Brenda L.; Silva, Gabriel A.; Dale, Anders M.; et al. (Frontiers in Cellular Neuroscience, 2021)
Voltage imaging and “all-optical electrophysiology” in human induced pluripotent stem cell (hiPSC)-derived neurons have opened unprecedented opportunities for high-throughput phenotyping of activity in neurons possessing unique genetic backgrounds of individual patients. While prior all-optical electrophysiology studies relied on genetically encoded voltage indicators, here, we demonstrate an alternative protocol using a synthetic voltage sensor and genetically encoded optogenetic actuator that generate robust and reproducible results. We demonstrate the functionality of this method by measuring spontaneous and evoked activity in three independent hiPSC-derived neuronal cell lines with distinct genetic backgrounds.